Perubahan kekuatan impak resin akrilik polimerisasi panas dalam perendaman larutan cuka apel - Suguh Bhaktiar Pribadi; Moh. Yogiartono; Titien Hary Agustantina (DiscoverSys Inc., 2010)
Acrylic resin being has been used in dentistry since 1946. Apple vinegar solutioncurrently popular as healthy supplement drink. It consists of tanin (fenol), acid, andother subtances. Fenol and acid are able to chemically damage to acrylic resin. Thepurpose of this study was to investigate the impact strength of heat cured acrylic resinafter immersed in apple vinegar solution. This experiment was carried out on the heatcured acrylic resin sample of size 65 x 10 x 2.5 mm. The immersion periods variedfrom 45 minutes, 11 days, and 17 days. There were 42 samples, divided into 21samples for three treatment groups and 21 samples for three control groups. Theresult showed that there were significant differences of acrylic resin strength afterimmersion in apple vinegar at 45 minutes and 17 days. The conclusion was the longerimmersion time of acrylic resin in apple vinegar would reduce the impact strength.